APLIKASI GAME FIRST PERSONAL SHOOTER (FPS) BERBASIS ANDROID - randi wijaya; Khairil Khairil; Ricky Zulfiandry (Jurnal Media Infotama, 2023)
Abstract:First Person Shooter (FPS) this game is usually a shooting game where the appearance is seen from the player’s eyes. Where each zombie object appears automatically then the user will try to shoot at the zombie object, so if the a zombie object is shot will increase the score value. Unity3d is an IDE display for free java/androiddevelopment. Meanwhile,according to safaat (2013:6) unity3d contains an IDE game engine used to make android coding. Unity3d is a supporting application for android development that is free. At the level of the game starts with an easy level by getting points and adventure, then the level will automatically go up. An alternative game to be able to provide games that are able to hone the brains ability in logic/mathematics and can implement the First Personal Shooter (FPS) game with an Android-based united3d game engine. It is hoped that the development of this application can be a reference not that the geofencing algorithm is not only be applied to map-based applications so that the geofencing algorithm can be applied to similar applications as information technology developments.